Optimal synthesis of QCA logic circuit eliminating wire‐crossings. Issue 3 (2nd March 2017) - Nath, Rajdeep Kumar; Sen, Bibhash; Sikdar, Biplab K.
Abstract : Wire‐crossing plays a pivotal role toward the progress of non‐complementary metal–oxide–semiconductor technology. Hefty amount of wire‐crossings leads to many complications including cross‐talk, colossal power dissipation and high cost function which in turn makes the fabrication difficult. In this regard, this work presents an efficient method for circuit implementation based on majority logic in quantum‐dot cellular automata (QCA) with optimum wire‐crossing. The authors' proposed method is able to eliminate wire‐crossing by the generation and routing of proper intermediate function in the circuit utilising the orientation of the input variable. An algorithm to minimise the number of wire‐crossing is also reported. Experimental results establish the effectiveness of the proposed method in circuit level also. Finally, a concrete framework to design a cost‐effective logic circuit in QCA ensuring the least/optimum wire‐crossing is established.